Investment Portfolio’s Including Different Cryptocurrencies Efficiency Study - Juskaite, Lina; Gudelyte-Zilinskiene, Laura; Tamosiuniene, Rima (Transformations In Business & Economics, 2024)
The development of technology and globalisation have opened wide opportunities even for investors without relevant knowledge or experience to use investment instruments. Although cryptocurrencies have unique features that attract investors, the market is also subject to risks: price fluctuations, operational risks, and the issue of trust. In this context, looking for effective solutions for investment portfolios and being able to understand better and evaluate the cryptocurrency market becomes especially important. Previous studies have highlighted the benefits of cryptocurrencies, such as diversification, hedging, and safe havens, but there is little research that reveals the performance of a cryptocurrency portfolio. Investors seek the highest possible return but generally avoid or underestimate risk. Applying portfolio optimisation in the study aims to identify cryptocurrencies, the inclusion of which in a traditional asset investment portfolio would help to achieve the most effective combination of desired return and risk. The primary purpose of this study is to evaluate the impact of different cryptocurrencies on the efficiency of the investment portfolio. Ten cryptocurrencies included in the B10 BITA CRYPTO 10 INDEX composition are studied. Due to the instability of cryptocurrencies, the composition of this index is constantly changing. The cryptocurrencies analysed in the study, included in the composition of this index, were fixed in August 2023. Traditional assets in the study are represented by stock indices: S&P 500, Euro Stoxx 50, DAX and CAC 40. After identifying efficient portfolios in the study, it can be concluded that the inclusion of different cryptocurrencies in an investment portfolio consisting of stock indices does not always allow efficient portfolio results to be achieved.
Keywords: cryptocurrency; diversification; efficient portfolio; portfolio optimisation; stock indices; traditional asset